Fetal hemangioma. - Bonifazi, E.; Mazzotta, F.; Laforgia, N. (European Journal of Pediatric Dermatology, 2003)
Clinical features. Fetal hemangioma completely matures “in utero”. This is why it can be shown by ultrasonography in the second trimester of pregnancy. Fetal hemangioma mainly affects the face and lower limbs. At birth it appears as a purplish, up to 15 cm in size tumor with ectatic vessels, sometimes with a central crust or ulceration. Pathological findings. Lobules of endothelial cells with some mitoses and large, thin-walled vessels stay within a densely fibrotic stroma. The latter contains deposits of hemosiderin and focal thrombosis and sclerosis. Unlike common hemangioma, its cells do not react with GLUT-1 and LeY antigens. Prognosis. Characteristically, fetal hemangioma is already fully developed at birth. It does not grow anymore and rapidly regresses within 6-18 months with atrophic scars.